Perlindungan Hukum bagi Pekerja Paruh Waktu dalam Keselamatan dan Kesehatan Melalui Program Jaminan Sosial Tenaga Kerja - I Kadek Surya Juliarnawa; I Puru Gede Seputra; Ni Made Puspasutari Ujianti (Jurnal Konstruksi Hukum, 2021)
Nowadayas, the increasing of economic growth requires individuals to try to make ends meet. The employment relationship between the business owner and his workers is regulated in a work agreement. In the current covid-19 pandemic, many companies are implementing part-time work to reduce company operating costs. This research examines two main problems, namely the regulation of health and safety laws for certain time workers, and legal protection of social security for certain time workers. Normative legal research is used in this research by examining problems based on the applicable legal basis in the form of statutory regulations and supported by theories from experts. The results showed that the legal basis regarding health and safety for part-time workers is regulated in Article 99 paragraph (1) of Law no. 23 of 2003 concerning Employment which regulates that every worker and his family has the right to obtain employment social security. Then, employment social security is regulated in Law no. 40 of 2004 concerning the National Social Security System (SJSN) and Law no. 24 of 2011 concerning BPJS. The implementation of social security is based on simultaneous efforts that are family and mutual in nature according to the mandate of the Pancasila and the 1945 Constitution of the Republic of Indonesia. Based on the research results, it can be concluded that in this case part-time workers do not really understand the protection of their rights as workers within a certain period of time. For this reason, this regulation on the protection of workers should be further disseminated to workers and business actors so that workers can obtain their rights in accordance with applicable regulations.